Demand for air cargo and demand for virtual commerce goods in Brazil - Rocha, Carlos Henrique; Mostardeiro, Priscila; Alves, Luiz Augusto Silva (Revista Gestão da Produção Operações e Sistemas, 2020)
Some studies have reported that current demand for air cargo transport has largely derived from the demand for goods in B2C-type electronic commerce. Marketing experts consider that consumer income bracket, cost of goods, freight costs and other less tangible factors influence consumer decisions to purchase online. This study makes an econometric investigation as to whether determinants of e-commerce demand in Brazil can explain the behavior of the demand for air cargo transport services. The study sample period is 2000 to 2016. Unit root and co-integration tests were conducted prior to the regression analysis of the results obtained for the air transport services demand as well as tests for correlation among explanatory variables for the air cargo demand. The reported results make it possible to conclude that the determinants of e-commerce demand do explain the demand for air cargo transport services. It is important to underscore that studies designed to determine the dimensions of cargo aircraft fleets and airport cargo terminals installed at airports or in their vicinities must always take into account the demand for goods offered by B2C-type e-commerce in their analyses.